Menanamkan Nilai-Nilai Agama Islam Di Sekolah Dasar : Studi Kasus Tentang Metode Pengajaran Efektif - Rinsi Dartati (GHAITSA : Islamic Education Journal, 2023)
Education is something that aims to explore a person's potential and skills in society. Instilling Islamic values since entering elementary school, children are still experiencing social, emotional and behavioral development to face future forgetting. Children at elementary school age still lack understanding and development of students' personalities. The aim of the research is to determine Islamic religious values in elementary schools in a case study of effective teaching methods. Analysis of the data used. Descriptive qualitative, using interview, observation and documentation methods. It finds out the validity of the data using source triangulation. To find out how students can understand and explore the potential of religion in elementary school, teachers carry out learning habits about the Islamic religion, memorizing short verses, reading the Qur'an and practicing prayer and telling stories of the prophet. So that students will easily accept the teaching pattern and habituate it to students which will have a positive impact on attitudes and behavior.